Performance of anterior nares and tongue swabs for nucleic acid, Nucleocapsid, and Spike antigen testing for detecting SARS-CoV-2 against nasopharyngeal PCR and viral culture. (April 2022) - Montaño, Michalina A.; Bemer, Meagan J.; Heller, Kate B.; Meisner, Allison; Marfatia, Zarna; Rechkina, Elena A.; Padgett, Leah R.; Ahls, Charlotte L.; Rains, Douglas; Hao, Linhui; Hsiang, Tien-Ying; Cangelosi, Gerard A.; et al.
Highlights: Polyester and FLOQSwabs perform in similar manner when testing for SARS-CoV-2. Tests using nasal swabs by RT-PCR were more sensitive than tests using tongue swabs for SARS-CoV-2. Self-collected nasal swabs are an accurate method for diagnosis of SARS-CoV-2. Abstract: Objectives: This study assesses and compares the performance of different swab types and specimen collection sites for SARS-CoV-2 testing, to reference standard real-time reverse transcriptase-polymerase chain reaction (RT-PCR) and viral culture. Methods: Symptomatic adults with COVID-19 who visited routine COVID-19 testing sites used spun polyester and FLOQSwabs to self-collect specimens from the anterior nares and tongue. We evaluated the self-collected specimen from anterior nares and tongue swabs for the nucleocapsid (N) or spike (S) antigen of SARS-CoV-2 by RT-PCR and then compared these results with results from RT-PCR and viral cultures from nurse-collected nasopharyngeal swabs. Results: Diagnostic sensitivity was highest for RT-PCR testing conducted using specimens from the anterior nares collected on FLOQSwabs (84%; 95% CI 68-94%) and spun polyester swabs (82%; 95% CI 66-92%), compared to RT-PCR tests conducted using specimens from nasopharyngeal swabs. Relative to viral culture from nasopharyngeal swabs, diagnostic sensitivities were higher for RT-PCR and antigen testing of anterior nares swabs (91-100%) than that of tongue swabs (18-81%). Antigen testing of anterior nares swabs had higher sensitivities against viral culture (91%) than against nasopharyngeal RT-PCR (38-70%). All investigational tests had high specificity compared with nasopharyngeal RT-PCR. Spun polyester swabs are equally effective as FLOQSwabs for anterior nasal RT-PCR testing. Conclusions: We found that anterior nares specimens were more sensitive than tongue swab specimens or antigen testing for detecting SARS-CoV-2 by RT-PCR. Thus, self-collected anterior nares specimens may represent an alternative method for diagnostic SARS-CoV-2 testing in some settings.